Morphological and Biochemical Parameters of Pigs’ Blood with Enzootic Pneumonia - Tazayan , Artur; Tambiev, Timur; Babkina, Tatiana (KnE Life Sciences, 2021)
One of the most common diseases of pigs in large pig enterprises is enzootic pneumonia. The main etiological agent causing enzootic pneumonia is Mycoplasma hyopneumoniae. Mycoplasmas have minimal virulence, but they increase the susceptibility of pigs to secondary infections. In association with other microorganisms, Mycoplasma hyopneumoniae enhances its pathogenic effect, which makes the course of the disease more severe, often leading to the death of animals. Blood tests were performed to study the changes in morphological and biochemical parameters during the development of infection caused by Mycoplasma hyopneumoniae. Experimental groups of animals were formed, consisting of healthy as well as infected and ill pigs of different ages (2, 3, and 4 months), in which the pathogen M. hyopneumoniae was detected by polymerase chain reaction. The following hematological changes were revealed in the piglets suffering from respiratory mycoplasmosis: erythropenia, leukopenia, increased blood sedimentation rate (BSR), hypoproteinemia, hypoalbuminemia, increased activity of alanine aminotransferase and alkaline phosphatase, increased urea, and hyperglycemia. Keywords: pigs breeding; pneumonia; biochemical parameters; morphological parameters